Serum Cystatin C, Markers of Chronic Kidney Disease, and Retinopathy in Persons with Diabetes - Chee Wai Wong; Boon Wee Teo; Ecosse Lamoureux; Mohammad Kamran Ikram; Jie Jin Wang; E. Shyong Tai; Sunil Sethi; Tien Yin Wong; Charumathi Sabanayagam (Journal of Diabetes Research)
Purpose. We examined the association of CKD defined by serum creatinine, serum cystatin C, and albuminuria with moderate diabetic retinopathy (DR). Methods. We examined 1,119 Indian adults with diabetes, aged 40–80 years, who participated in the Singapore Indian Eye Study (2007–2009), a population-based cross-sectional study. The associations of CKD defined by each of the three markers alone and in combination with moderate DR were examined using logistic regression models adjusted for potential confounding factors including duration of diabetes, smoking, body mass index, systolic blood pressure, and HbA1c. Results. The prevalence of moderate DR was significantly higher among those with CKD defined by triple markers (41.1%) compared to CKD defined separately by creatinine (26.6%), cystatin C (20.9%), and albuminuria (23.4%). People with CKD defined by triple markers had a fourteenfold higher odds of moderate DR (OR (95% CI) = 13.63 (6.08–30.54)) compared to those without CKD by any marker. Nearly half (48.7%) of participants with cystatin C ≥ 1.12 mg/L have moderate DR. Conclusions. CKD defined by a triple marker panel was strongly associated with moderate DR in this Asian population with diabetes.